Effect of online courses on US college students’ knowledge about health disparities - Njoku, Anuli (Health Education Journal, 2019)
Objective: To describe faculty efforts to deliver and evaluate health disparities–related education in US online undergraduate and graduate public health courses. Design: A pre- and post-survey was given to a cohort of 46 US college students in three public health courses taught asynchronously online over an 8-week period in 2017. This study took place at a mid-sized, public, rural, midwestern US university. Method: Faculty received professional development and online training and were assigned to develop courses for a new public health programme. Following the receipt of ethical approval, students completed anonymous, online pre- and post-surveys to assess effect of intentional instructional approaches on their knowledge and attitudes about health disparities. Curricula incorporated various assessment methods and teaching strategies. Descriptive statistics were used to compare pre- and post-survey scores and analyse demographic data. Paired t-tests and one-way analysis of variance were used to analyse pre- and post-survey test scores. Results: At post-survey, students demonstrated a positive change in mean scores for several items, including for ability to discuss the role of theory in understanding health behaviour and disparities in health status (3.20 vs 4.06; p < .001) and ability to discuss strategies health promotion programmes can use to reduce health disparities (3.47 vs 4.40; p < .001). Post-survey response rate was 87%. Conclusion: Results suggest an effective way to increase health disparities knowledge among online college students. Additional research is encouraged to expand upon these findings.
Keywords: dept.pch; peer-reviewed